The Convergence of Artificial Intelligence and Electronic Devices for Rapid Food Quality Measurement: A Systematic Review - Mohammad Alfiza Rayesa; Dego Yusa Ali; Neza Fadia Rayesa; Elsa Lolita Anggraini; Togi Siholmarito Simarmata (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
Ensuring the quality and safety of food is a critical global challenge intensified by complex supply chains and increasing consumer demand for transparency. Traditional measurement techniques—ranging from microbial plating to sensory panels- are often destructive, time-consuming, labor-intensive, and expensive. Recently, non-invasive electronic sensing technologies, coupled with Artificial Intelligence, have emerged as powerful alternatives for rapid and objective assessment. This review aims to identify, synthesize, and appraise peer-reviewed research published between 2005 and 2025 that incorporates AI into electronic devices: electronic noses, computer vision, and spectroscopy for food quality measurement. A systematic literature search was conducted across ScienceDirect, SpringerLink, and IEEE Xplore. The review followed the PRISMA guidelines by identifying 63 studies that met strict inclusion criteria for integrating sensing, hardware, and machine learning algorithms. Analyses show that Computer Vision Systems (CVS), Hyperspectral Imaging (HSI), and Electronic Noses (e-noses) technologies. Deep Learning, in particular Convolutional Neural Networks (CNNs), has surpassed traditional machine learning techniques, such as SVM and PCA, in performance. Key applications include ripeness grading of fruits, detection of adulteration in powders, and freshness monitoring of vegetables and meat products. Integrating AI with electronic sensors provides a scalable, accurate, and non-destructive path forward for Industry 4.0 in the food sector. However, challenges to the issues of model interpretability, data standardization, and real-world robustness remain.